Assessment of the cluster potential of the agricultural equipment and parts manufacturing in Northern Mindanao - Banal, Ruel Vincent C.; Posadas, Roger (Quezon City University of the Philippines Diliman, 2012)
Industry clusters have become a popular concept in local and regional development. A cluster approach helps firms achieve a competitive advantage by promoting their common interests, and can make the public sector more effective in supporting the economy. It enables the firm and government identify the most promising opportunities to encourage further innovation, develop particular worker skills, and address issues that affect productivity. Equipment and parts manufacturing is a strategic industry which offers machinery equipment and/or parts particularly in the agro-industrial sector. With the advocacy of the government to employ industry clustering as one of the strategies in advancing the metalworking industry in region 10 and its commitment to support particularly the metalworking organization, there is a need to seriously assess the potential of the development of the agro-equipment and parts manufacturing and understand the impact of industry clustering in the region. The study aims to assess and evaluate the current problems besetting the metal industry of Northern Mindanao, identify product niches for the agricultural equipment and parts manufacturing cluster considering the existing capabilities of the metalworking firms and develop logical framework for the development of a globally-competitive agro-equipment and parts manufacturing cluster. Porter provides an industry cluster framework to explain the determinants of regional competitive advantage. If a region succeeds in developing an industry-specific diamond, then the region's industry cluster will be competitive in the global economy because individual firms belonging to the cluster will draw on specialized services, inputs, and related industries. The four components of the diamond are : Firm strategy and rivalry, Demand conditions, Related and supporting industries and Factor conditions. The study will identify and assess the present condition and specific needs of the metalworking industry in region 10. Identify product niches for the agro-equipment and manufacturing cluster with consideration of the existing capabilities of the metalworking firms. Develop a logical framework for the development of a globally-competitive agro-equipment and parts manufacturing cluster. The study covers Cagayan de Oro area where majority of actors of the metal industry are situated and where growth of industries and economic development are visible. Government interventions to the metalworking industry begain in 1979. In 1987, industry clustering was conceived by the government through the Department of Trade and Industry. Other government agencies also supported the metalworking industry in region 10 and a number of laws and regulations that affect the metalworking industry were formulated. The survey of twenty nine (29) firms revealed that eleven (11) firms, which comprises 38 percent were established in the 1990s while there were only three (3) firms established before 1980. Majority of these business firms are single proprietorship. Most of the corporate firms are 15 years or more in the industry. Only three (3) firms are classified as medium. Production personnel revealed that the metalworking industry is male dominated industry with 93 percent of the workforces are men. Majority of the equipment used in the firms are second hand imported equipment although there are a handful of firms which bought new imported equipment. Some of the firms likewise, use locally made equipment for their processes. The analysis suggests that the industry cannot be called yet as full-pledged industry cluster. The reason is that there are uncertainties as to whether the industry has reached critical mass of competitors and research competence is not yet established.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Agricultural equipment--Northern Mindanao; Farm equipment -- Mindanao Island (Philippines); Parts manufacturing; Northern Mindanao